The effect of Ultraviolet-B irradiation on the photodegradation of ciprofloxacin and norfloxacin as inhibitors of bacterial DNA replication and cell division in urea medium - Alhassani, Ansam; Alnakshbandi, Abdulkadir A.; Al-Nimer, Marwan S. (Cellular and Molecular Biology, 2020)
Ciprofloxacin hydrochloride and Norfloxacin are second-generation fluoroquinolone antibiotic against bacterial DNA gyrase, which reduces DNA strain throughout replication. As DNA gyrase is essential through DNA replication, subsequent DNA synthesis and cell division are inhibited. Direct photolysis of fluoroquinolones was studied by using UV irradiation in the presence or absence of other substances that generate free radicals. This study aimed to assess the effect of Ultraviolet B (UVB) irradiation in removing ciprofloxacin and norfloxacin by using a simulating model of wastewater contained urea at pH 4. A known concentration of ciprofloxacin and norfloxacin were prepared in an appropriate aqueous solution in presence or absence 0.2M urea and adjusted at pH 4. The dissolved drugs were irradiated with UVB-lamp in a dark place for 60 minutes. The percent of removal and the rate of elimination (k) of each drug were calculated. The direct photolysis effect of UVB irradiation was observed with ciprofloxacin which amounted to 24.4% removal compared with12.4% removal of norfloxacin after 60 minutes of irradiation. The effect of UVB irradiation was enhanced by urea to reach 38.9% and 15% for ciprofloxacin and norfloxacin. The calculated k of ciprofloxacin has amounted to three folds of that of norfloxacin. Direct photolysis of ciprofloxacin and norfloxacin can be achieved simply by using a simulation model of 0.2 M urea and UVB irradiation at pH 4. UVB is highly effective in removing ciprofloxacin compared with norfloxacin by 2-3 folds.